Multi-Omics Revealed the Effects of Different Feeding Systems on Rumen Microorganisms, Cellulose Degradation, and Metabolites in Mongolian Cattle - Kexin Jiang; Jianfei Ma; Junzhao Xu; Ying Zhang; Huaxin Niu (Animals)
Rumen microbiota is crucial for cellulose degradation and nutrient metabolism in ruminants. Different feeding systems like grazing and housed feeding can significantly impact it. Mongolian cattle show unique cellulose degradation ability, but functional changes under different feeding conditions are unclear. This study aims to investigate the effects of grazing and housed feeding on rumen microbiota, cellulose degradation, and metabolism in Mongolian cattle. In a 90-day trial, 12 female Mongolian cattle were divided into grazing (F group) and housed feeding (S group). Rumen samples were collected to analyze fermentation parameters, enzyme activities, microbiomes, and metabolomes. The F group had higher acetate, cellulase, xylanase, and β-glucosidase activities (p < 0.05). Bacteroidota and Prevotella were more abundant (p < 0.05), while Firmicutes and Ruminococcus were less abundant (p < 0.05) in the F group. Carbohydrate metabolic pathways and CAZymes (GH2, GH10) were upregulated in the F group, while the S group had enriched purine metabolic pathways and CAZyme (GH31). A total of 64 differential metabolites were found, with subaphylline upregulated in the F group and L-arogenate in the S group (p < 0.05). Grazing increased cellulose degradation and subaphylline production in Mongolian cattle, while housed feeding improved starch utilization efficiency and fat synthesis. These findings provide a basis for optimizing feeding strategies and improving fibrous feed resource utilization in Mongolian cattle.